Il tragico, il comico e il grottesco nella lingua di alcune opere verdiane - Ilaria Bonomi (Itinera, 2013)
In this contribution I report the linguistic reflections of the cathegories of the ugly and the grotesque in some Verdi’s libretti. Respect to the ugly, I concentrate my analysis on Solera’s libretti, particularly on Lombardi, in the first phase of Verdi’s composition process. Respect to the grotesque, the admixture between tragic and comic find its most convincing expression in the synergy between words and music in: Rigoletto, La forza del destino di Piave, Ballo in maschera di Somma. Here the stylistic variation among different carachters seems good dashed and well conducted by Verdi and the two librettists. Il trovatore, on the contrary, is few diversified in linguistic registers and in contrasts and it is characterized by a strongly elevated linguistic.